The Effect of Village Head Leadership on Human Resource Development in Sadasari Village : Pengaruh Kepemimpinan Kepala Desa terhadap Pengembangan Sumber Daya Manusia di Desa Sadasari - Gustman Nurjayansah Rahmani; Subhan Agung (Jurnal Pemerintahan dan Politik, 2026)
Purpose: The purpose of this study is to examine the impact of the village head’s leadership on human resource development in Sadasari Village, Argapura Subdistrict, Majalengka Regency. Methodology: This study employed a quantitative approach using multistage random sampling; the total study population was 3,624 people, and a sample of 360 people was obtained. Data were collected via a questionnaire that had been tested for validity and reliability, then analyzed using simple linear regression, the coefficient of determination (R²), and hypothesis testing, all processed using statistical software. Findings: The results of this study indicate that the village head’s leadership has a positive and significant influence on human resource development. The R² test results show an R² value of 0.461%, indicating that 46.1% of human resource development in Sadasari Village is influenced by the village head’s leadership, while the remaining 53.9% is influenced by other variables not examined by the researcher in this study. Practical Implication: This study offers practical benefits for village governments and policymakers in enhancing local leadership capacity. Human resource development programs can be successfully implemented when village heads possess strong social capital within their communities. Trust, social networks, and collaboration are crucial for sustainable village development. Originality/Value: The novelty of this study lies in the use of social capital theory, based on quantitative analysis, to examine the role of village heads and human resource development at the village level.